Les Mosquées Ibadites Du Djebel Nafūsa Architecture, histoire et religions du nort-ouest de la Libye (VIIe-XIIIe siècle) - Prevost, Viginie (Society for Libyan Studies, 2016)
The mosques of the Djebel Nafūsa, little known and under threat, personify the continuity of traditions and faith of the Ibadites, who have retained their grip over the centuries on this rugged landscape, despite their many trials and tribulations. This book is the result of a mission carried out in 2010 with the photographer Axel Derriks and examines twenty or so mosques, bringing to light their architectural features and linking them to medieval Ibadite texts.